TO STUDY THE DRUG UTILIZATION PATTERN OF ANTIBIOTICS IN POST-OPERATIVE PATIENTS IN THE DEPARTMENT OF OBSTETRICS AND GYNECOLOGY AT TERTIARY CARE TEACHING HOSPITALS. - LATHA C, DEEPA; B, LALITYA; G, VIJAYALAKSHMI; G, VIJAYALAKSHMI (Innovare Journal of Life Sciences, 2017)
ABSTRACT: Objectives: The study is carried out to determine possible irrational use of drugs,antibiotic sensitivity pattern,minimize adverse events,drug-drug interactions. Methodology: It is a prospective observational study carried out in department of Obstetrics and Gynecology, Bhaskar General Hospital after obtaining permission from the institutional human ethics committee. It is carried out on 50 patients of post-operative cases for duration of two months by obtaining their case-sheet data. The prescriptions were assessed for patient's demographic data, antimicrobial preference, dose, duration, route of administration, categorization of drugs according to FDA, rationality score as per WHO, prescribing indicators score as per WHO. Results: The average number of drugs per patient is 3. The most frequently prescribed drugs were Metronidazole (dose:400mg-TID;100%), Tinidazole (dose:500mg-BD;90%), Ceftriaxome (dose:200mg-BD;100%),Amoxicillin+Clavulinic acid (dose:625mg-TID;14%).The brand drugs used are 100%,Generic drugs-0%, Essential drugs-87.5%,Non essential drugs-12.5%,Category B drugs-100%. Conclusion: Drug use pattern is rational with few exceptions. All the drugs were prescribed according to FDA category B. Hence we conclude that 20% of prescriptions were under polypharmacy and 80% were according to prescription indicator of WHO.